Caseous calcification of mitral annulus - Kuwauchi, Shintaro; Watanabe, Sunao; Abe, Kohei; Yamasaki, Manabu; Ito, Joji; Mizuno, Atsushi; Kawazoe, Kohei (Cardiovascular Diagnosis and Therapy, 2013)
Caseous calcification of the mitral valve annulus (CCMA) is a rare variant of mitral annular calcification (MAC) (1). Because it is similar in appearance to lesions such as a cyst, a thrombus, a tumor, or an abscess, misdiagnoses and unnecessary surgical treatments have been reported. It is therefore important to consider CCMA in the differential diagnosis of other similarly appeared lesions. We report a 69-year-old man with CCMA detected incidentally by the intraoperative transesophageal echocardiography during coronary artery bypass grafting.